(NsKORO BUDET BURQ (B:s (NrOMAN (B/s - (NdVOJS(B, (NgR\Ms; (NqHONTOWA(B, (NwERAs ((NsANKT(B-(NpETERBURG (B:s (NaZBUKA(B-(NKLASSIKA(B,s, 2003)
(NgR\M dVOJS RODILSQ W (B1954 (NG(B. (NW SEMXE ANGLIJSKOGO [AHTERA BLIZ kOWENTRI(B. (NlAUREAT LITERATURNYH PREMIJ(B. (Nw DANNOM ROMANE BOLX[AQ KOMPANIQ ANGLI^AN PRIEZVAET OTDYHATX NA @G fRANCII(B.s